Human immunodeficiency virus/acquired immunodeficiency syndrome knowledge among followers of various religions in India - Asima Karim; Rizwan Qaisar; Amna Khalid; Firdos Ahmad; M Azhar Hussain (Wolters Kluwer Medknow Publications, 2024)
Introduction: Effective educational interventions to knowledge, attitude, and prevention of human immunodeficiency virus/acquired immunodeficiency syndrome (HIV/AIDS) may limit the spread of the disease. However, the relevance of HIV knowledge to followers of religions is unknown. We assessed the 2015-2016 Demographic and Health Survey (DHS) data from India to investigate the levels of knowledge of HIV/AIDS among Hindus, Muslims, Sikhs, Christians, and Buddhists in relation to standard sociodemographic variables in India. Methods: We used the individual and household level data from the internationally and temporally harmonized cross-sectional DHS. These data were representative of the national population and were collected from January 2015 to December 2016. Results: The age range of the population was 15-54 years (n = 224,531). We found the highest level of knowledge of HIV/AIDS among Sikh men (than the followers of other religions (80.4%-92.7%). Conversely, Muslims and Hindus were least knowledgeable of HIV/AIDS (80.4% and 81.2%). Younger participants (82.5%), residents of urban areas (90.6%), more educated (98.6%), never married (84.9%), wealthier (95.5%), and having more access to mass media (90.4%-96.7%) were more aware of HIV/AIDS-related knowledge. Among various religions, Sikhs were more educated (16.1% with higher education), wealthier (59.5% in the top quintile), with higher exposure to communication means than Muslims, Hindus, and Christians. Conclusion: We report that Sikh men are most knowledgeable of HIV compared to Sikh women and followers of other religions. Our findings may help formulate public health strategies targeting various religious groups to reduce the incidence of HIV/AIDS.